2021
DOI: 10.3389/fcell.2021.640319
|View full text |Cite
|
Sign up to set email alerts
|

The Elusive Endometrial Epithelial Stem/Progenitor Cells

Abstract: The human endometrium undergoes approximately 450 cycles of proliferation, differentiation, shedding and regeneration over a woman’s reproductive lifetime. The regenerative capacity of the endometrium is attributed to stem/progenitor cells residing in the basalis layer of the tissue. Mesenchymal stem cells have been extensively studied in the endometrium, whereas endometrial epithelial stem/progenitor cells have remained more elusive. This review details the discovery of human and mouse endometrial epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 111 publications
(176 reference statements)
2
53
0
Order By: Relevance
“…In addition, Axin2 + cells can form fully functional endometrial organoids in vitro [ 107 ]. The above findings seem to provide evidence for the involvement of the mesenchymal-to-epithelial transition (MET) in the maintenance and regeneration of the uterine epithelium [ 109 ]. However, a recent cell fate tracing study found that the conclusive evidence for the conversion of mesenchymal cells to epithelial cells in adult uterine is lacking.…”
Section: Endometrial Epithelial Stem/progenitor Cellsmentioning
confidence: 99%
“…In addition, Axin2 + cells can form fully functional endometrial organoids in vitro [ 107 ]. The above findings seem to provide evidence for the involvement of the mesenchymal-to-epithelial transition (MET) in the maintenance and regeneration of the uterine epithelium [ 109 ]. However, a recent cell fate tracing study found that the conclusive evidence for the conversion of mesenchymal cells to epithelial cells in adult uterine is lacking.…”
Section: Endometrial Epithelial Stem/progenitor Cellsmentioning
confidence: 99%
“…We found that the plexus network remained behind in all menstrual samples observed, which demonstrates that this is a major component of the basalis ( Figure 3 , Video S2 ). Although previous scanning electron microscope studies have shown that the endometrium sheds in a piecemeal manner with denuded and intact sections next to each other [ 42 ], our study has demonstrated that the functional layer of the endometrium sheds off completely during menstruation, probably due to a limited area where we assessed 3D structure [ 29 ].…”
Section: 3d Structure Of the Endometriummentioning
confidence: 76%
“…ASC infusion also decreased pro-in ammatory and probrotic cytokine expression but did not alter the expression of anti-in ammatory cytokines, matrix metalloproteases, angiogenetic factors, or estrogen and progesterone receptors. Endometrial stem cells, which are located in the basalis layer, differentiate into the endometrial stroma, epithelium, and endothelium [39]. After the infusion of bone-marrow cells with mTert-GFP or Ch β-actin GFP, all GFP-positive cells in the endometrium are immune cells, including T cells and macrophages, suggesting that bone-marrow stem cells do not contribute to endometrial cell lineages [40].…”
Section: Discussionmentioning
confidence: 99%